الفكر المقاصدي المعاصر وتوظيفه في الصناعة الفقهية : دراسة الأفكار المقاصدية التأسيسية عند أحمد الريسوني - Saputra, Refki (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Maqashid sharia has transformed into an independent scientific discipline through some developments from late scholars. They took part in constructing the concept of maqashid sharia, outlining the epistemological foundation and the mechanism of its implementation. This research aims to examine the basis of the thoughts and ideas of Ahmad Ar-Raisuni, one of the central figures of contemporary maqashid sharia. Ar-Raisuni has made a great contribution to the maqashid of sharia both academically, theoretically, and practically. Ar-Raisuni not only called for the actualization of maqashid sharia in the construction and formulation of fiqh, but also prioritized the basic thoughts and ideas of the concept of maqashid sharia, actualized the maqashid approach in ijtihad, and formulated the scientific methodology of fiqh with the maqashid approach. This article employs a qualitative approach by exploring the main ideas of Ar-Raisuni in his works. This research concludes some of Ar-Raisuni's principal thoughts: the style of maqashid sharia thought, ijtihad based on the maqashid approach, analysis of objectives and orientation to the benefit of law, and the development of a law enforcement methodology that collaborates: text, purpose and reality, as well as formulating the principles of maqashid sharia.